Differential mesenteric fat deposition in bovines fed on silage or concentrate is independent of glycerol membrane permeability - Martins, Ana Paula (2011)
In the meat industry, the manipulation of fat deposition in cattle is of pivotal importance to improve production efficiency, carcass composition and ultimately meat quality. There is an increasing interest in the identification of key factors and molecular mechanisms responsible for the development of specific fat depots. This study aimed at elucidating the influence of breed and diet on adipose tissue membrane permeability and fluidity and their interplay on fat deposition in bovines. Two Portuguese autochthonous breeds, Alentejana and Barrosã, recognized as late and early maturing breeds, respectively, were chosen to examine the effects of breed and diet on fat deposition and on adipose membrane composition and permeability. Twenty-four male bovines from these breeds were fed on silage- or concentrate-based diets for 11 months. Animals were slaughtered to determine their live slaughter and hot carcass weights, as well as weights of subcutaneous and visceral adipose depots. Mesenteric fat depots were excised and used to isolate adipocyte membrane vesicles where cholesterol content, fatty acid profile as well as permeability and fluidity were determined. Total accumulation of neither subcutaneous nor visceral fat was influenced by breed. In contrast, mesenteric and omental fat depots weights were higher in concentrate-fed bulls relative to silage-fed animals. Membrane fluidity and permeability to water and glycerol in mesenteric adipose tissue were found to be independent of breed and diet. Moreover, the deposition of cholesterol and unsaturated fatty acids, which may influence membrane properties, were unchanged among experimental groups. Adipose membrane lipids from the mesenteric fat depot of ruminants were rich in saturated fatty acids, and unaffected by polyunsaturated fatty acids (PUFA) dietary levels. Our results provide evidence against the involvement of cellular membrane permeability to glycerol on fat accumulation in mesenteric fat tissue of concentrate-fed bovines, which is consistent with the unchanged membrane lipid profile found among experimental groups.